Psychological maltreatment and self-compassion - the mediating role of shame and perspective-taking - Vizin, G.; Szőcs, H.; Illyés, Z. (European psychiatry, 2022)
IntroductionPsychological maltreatment such as emotional abuse or neglect is a serious risk factor for poorer mental and somatic health outcomes in life. A higher rate of psychological maltreatment experienced in childhood is a predictor of aversive emotional states such as shame, and can negatively influence factors of mentalization such as perspective-taking capacity in adulthood. However, emotional abuse or neglect are also negative predictors of self-compassion.ObjectivesThe purpose of the study was to test two mediating models. We hypothesized, that reduced perspective-taking capacity, as well as higher levels of shame due to psychological maltreatment can be causally linked to lower levels of self-compassion.MethodsWe collected data from 120 healthy subjects (mean age=29.46, SD = 7.55) from Hungary We used Experience of Shame Scale, Interpersonal Reactivity Index, Childhood Trauma Scale, and the Self-Compassion Scale in our cross-sectional questionnaire study.ResultsPsychological maltreatment is a significant negative predictor of self-compassion (b=-0,712; p<0.05), and shame seems to play a mediating role in this relationship (effect size= 0.231; p<0.05). Psychological maltreatment was not a statistically significant predictor of perspective-taking.ConclusionsOur results highlight that shame has a central role between childhood traumatization and psychological well-being. In the case of early emotional maltreatment we have to focus on shame for higher levels of self-compassion and effective healing in psychotherapy.DisclosureNo significant relationships.